2020
DOI: 10.1155/2020/8674512
|View full text |Cite
|
Sign up to set email alerts
|

Multiagent Reinforcement Learning-Based Taxi Predispatching Model to Balance Taxi Supply and Demand

Abstract: With the improvement of people’s living standards, people’s demand of traveling by taxi is increasing, but the taxi service system is not perfect yet; taxi drivers usually rely on their operational experience or cruise randomly to find passengers. Without macroguidance, the role of the taxi system cannot be fully utilized. Many scholars have studied taxi behaviors to find better operational strategies for drivers, but their researches rely on local optimization methods to improve the profit of drivers, which w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 34 publications
0
15
0
Order By: Relevance
“…Previous studies on taxi demand prediction are generally based on historical taxi trajectory data. Previous studies have shown the feasibility of obtaining predictions from historical taxi trajectory data [1,[5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23]. Methods of traffic demand prediction can be classified into three types: linear system theory (such as the autoregressive moving average model [24], Kalman filtering model, and time series model), nonlinear system theory (such as the neural network model, gray prediction model, and random forest model (RFM)), and combination forecasting model (CFM).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies on taxi demand prediction are generally based on historical taxi trajectory data. Previous studies have shown the feasibility of obtaining predictions from historical taxi trajectory data [1,[5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23]. Methods of traffic demand prediction can be classified into three types: linear system theory (such as the autoregressive moving average model [24], Kalman filtering model, and time series model), nonlinear system theory (such as the neural network model, gray prediction model, and random forest model (RFM)), and combination forecasting model (CFM).…”
Section: Introductionmentioning
confidence: 99%
“…The first agent-based dispatch model can be called as limited-movement-grid (LMG) model [9]. In it, the map is divided into square-shaped grids with specified size.…”
Section: Related Work 21 Online Taxi Dispatch Systemmentioning
confidence: 99%
“…This dispatching model is then implemented into online taxi dispatch system simulation. In this simulation, the proposed model is compared with the stable marriage [5], limited-movement-grid [9], freemovement-grid [21], circle-shaped-maximumrevenue [17], and circle-shaped-nearest [22] models. These second to fifth models are the agent-based models explained in the related work section.…”
Section: Simulationmentioning
confidence: 99%
See 2 more Smart Citations